Digital Libraries and Archives 8th Italian Research Conference, IRCDL 2012, Bari, Italy, February 9-10, 2012, Revised Selected Papers - Italian Research Conference on Digital Libraries (Communications in Computer and Information Science, 2013)
This book constitutes the thoroughly refereed proceedings of the 8th Italian Research Conference on Digital Libraries, held in Bari, Italy, in February 2012. The 22 full papers, included together with 4 panel papers, were selected from extended versions of the presentations given at the conference, following an additional round of reviewing and revision after the event. The topics covered are as follows: legacy documents and cultural heritage; systems interoperability and data integration; formal and methodological foundations of digital libraries; semantic web and linked data for digital libraries; multilingual information access; digital library infrastructures; metadata creation and management; search engines for digital library systems; evaluation and log data; handling audio/visual and non-traditional objects; user interfaces and visualization; digital library quality; policies and copyright issues in digital libraries; scientific data curation, citation and scholarly publication, user behavior and modeling; and preservation and curation.